The Effect of Budget Variance on Changes in Regency/City Expenditure Budgets in South Sumatra - Errika; Sari, Yuliana; Oktarini, Kurnia Widya (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study analyzes the impact of variations in expenditure and revenue budgets on changes in expenditure budgets in district / city governments in South Sumatra. The sample was divided into 11 districts and 4 cities using purposive sampling technique. Data processing used a multiple regression statistical approach with multiple variables as well as classical assumption testing operated through the SPSS version 26 program. The research findings revealed that expenditure budget variation had a partially significant negative impact on budget changes, while revenue variation showed a significant positive influence. Simultaneously, however, both variables had a significant impact on budgetary changes. This study is expected to be a suggestion for local governments to form more appropriate budget policies, as well as an additional reference for further research in the field of local financial management.